Pendampingan Pastoral yang Memberdayakan Penyintas Sinabung yang Mengalami Trauma - Indah Sriulina (Indonesian Journal of Theology, 2016)
Hidden trauma within the survivors of an erupting Mount Sinabung has made it difficult for survivors to think objectively about the future—a limitation that has "contaminated" them, with regard to the past. Concerning this disaster, ongoing from 2010 until now, the urgency for physical relocation is clear. Nevertheless, this remains an unheeded warning. To address this issue, the author articulates here a method of pastoral care with the intent to affect physical relocation. Rather than rushing ahead to the end result, the author instead forwards an alternative approach, namely, the relocation of memory. Relocation of memory describes a method of pastoral care that assists in recognizing the danger to come if survivors remain unwilling to undergo physical relocation. Relocation of memory thus helps survivors to realize that life moves on, even with certain trauma.